1997
DOI: 10.1159/000159235
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Does Not Induce the Calcium-Dependent Nitric Oxide Synthase in Cultured Human Uterine Endothelial and Myometrial Smooth Muscle Cells

Abstract: In many tissues, estrogen-induced vasodilatation is mediated, at least in part, by the release of nitric oxide (NO). We determined whether human myometrial endothelial and smooth muscle cells express estrogen receptors (ERs) and whether endothelial NO synthase (eNOS) expression in these cells was affected by 17β-estradiol (10–13–10–6M). ER was strongly expressed in myometrial smooth muscle cells but was absent from endothelial cells. Expression of eNOS mRNA was strong in endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…25 In regard to the effect of estrogen on eNOS, many investigators have reported that estrogen up-regulates eNOS expression. By contrast, Zervou et al 12 and Tschugguel et al 26 could not demonstrate up-regulation of eNOS expression by estrogen. Activation of eNOS is induced by cytokines, such as transforming growth factor-b, 27 and expression of eNOS is inhibited by tumor necrosis factor-a.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…25 In regard to the effect of estrogen on eNOS, many investigators have reported that estrogen up-regulates eNOS expression. By contrast, Zervou et al 12 and Tschugguel et al 26 could not demonstrate up-regulation of eNOS expression by estrogen. Activation of eNOS is induced by cytokines, such as transforming growth factor-b, 27 and expression of eNOS is inhibited by tumor necrosis factor-a.…”
Section: Discussionmentioning
confidence: 82%
“…By contrast, Zervou et al 12 . and Tschugguel et al 26 . could not demonstrate up‐regulation of eNOS expression by estrogen.…”
Section: Discussionmentioning
confidence: 83%
“…HMMECs were isolated as described previously (21) with some modifications (see Supplemental Materials and Methods). The experiments were conducted on passage-four HMMECs, which were cultured as described in Supplemental Materials and Methods.…”
Section: Endothelial Cell Preparationmentioning
confidence: 99%
“…Estrogen has been shown to increase the level of ecNOS mRNA in cultured pulmonary artery endothelial cells (36) and in uterine arteries (56). However, estrogen was not shown to increase ecNOS mRNA in cultured human myometrial or bovine aortic endothelial cells (52). A recent study by Kleinert et al (29) provides direct evidence for a 1.8-fold increase in ecNOS protein expression by physiological levels of estrogen in cultured human endothelial cells.…”
Section: Ecnos Activity Is Elevated In Coronary Arteries From Female mentioning
confidence: 99%